Answer:
Step-by-step explanation:
-4 is really -1 * 4
-4² = -1 * 4²
-4² = -1 * 16
-4² = -16
Use parenthesis to square
(-1 * 4)² = (-4)²
(-4)² = 16
22+24+26+28+30+32+34+36+38+40+42+44= 396
Answer:
recursive: f(0) = 7; f(n) = f(n-1) -8
explicit: f(n) = 7 -8n
Step-by-step explanation:
The sequence is an arithmetic sequence with first term 7 and common difference -8. Since you're numbering the terms starting with n=0, the generic case will be ...
recursive: f(0) = first term; f(n) = f(n-1) + common difference
explicit: f(n) = first term + n·(common difference)
To get the answer above, fill in the first term and common difference values.
Answer:
B
Step-by-step explanation:
The second one!!!
<span>A water tank is 1/8 full. The tank is 3/4 full when 42 gallons are added to the tank. How much water was originally in the tank? (I rewrote it, your wording was messed up)
3/4 = 6/8
1/8 + 6/8 = 7/8 = 42 gallons
42 divided by 8 = 5 1/4
So, the answer is 5 1/4. The tank originally 5.25 gallons of water.</span>